Treatment of Benign Lesion of Levels I or II of the Parotid Gland: Long Term Results of Partial Superficial Parotidectomy. Issue 3 (29th May 2022) - Visconti, Irene Claudia; lannella, Giannicola; Meccariello, Giuseppe; Cammaroto, Giovanni; Gulotta, Giampiero; Greco, Antonio; de Vincentiis, Marco; Magliulo, Giuseppe; Pelucchi, Stefano; Maniaci, Antonino; Cocuzza, Salvatore; La Mantia, Ignazio; et al.
Abstract : Abstract: The correct surgical approach to benign parotid gland tumors is still matter of debate, it should be chosen considering the possibility of local recurrence or facial nerve complications in case of "not necessary" facial nerve dissection. In the era of minimally invasive surgery, more sparing approaches such as extracapsular dissection or partial superficial parotidectomy (P SP) are gaining popularity. The aim of the study is to present surgical results and long-term outcomes of PSP (level i or ii) in a large group of patients. Six hundred fifty-one patients who underwent parotid surgery between 2004 and 2020 were initially considered. Five hundred forty patients with benign lesions treated with PSP, enucleation, ECD were enrolled. Clinical features, surgical data, postoperative scarring, seroma, dehiscence, neuroma, outcomes as Frey syndrome, and delayed facial nerve dysfunction have been evaluated. 65.5% PSP, 25.2% enucleation, and 9.2% extracapsular dissection. No statistical difference in surgical time has been found (P 0.16). P   >  0.05 for seroma, neuroma, Frey syndrome, and facial palsy between different type of surgery. Frey syndrome in PSP: 6/135 (4.4%) in 2004 to 2012 and 2/219 (0.9%) in 2013 to 2020. The reduction between periods is significant (P  < 0.04). Recurrence: 0.8% (3/354) for PSP patients, 3.4% (5/ 136) in enucleation and 10% (5/50) in ECD (P  = 0.02). Partial superficial parotidectomy can be considered a minimally invasive and quick procedure with low complication rate. Our data seem to support this statement (large case series and long-term follow-up).